Beta 2-adrenergic mechanisms in experimental arthritis. - Levine, J D (1988)
We have studied (i) the contribution of specific adrenergic receptors to the proinflammatory effects of the sympathetic nervous system in experimental arthritis and (ii) the phases of the disease during which the sympathetic nervous system influences joint injury. Severity of joint injury was measured radiographically 28 days after induction of adjuvant arthritis in control rats and in rats treated with a variety of sympatholytic agents at various times during the course of the disease. Rats treated with a nonspecific catecholamine depletor (reserpine) or a beta-adrenergic receptor antagonist (propranolol) had a delayed onset and significantly less severe joint injury than saline-treated controls when treatment began prior to injection of the adjuvant and continued to day 28 after the injection. When administered over the same treatment period, neither nonselective (phenoxybenzamine) nor selective [prazosin (alpha 1) and yohimbine (alpha 2)] alpha-adrenergic receptor antagonists affected the onset or severity of joint injury. Metoprolol, a beta 1 antagonist, was also without effect. In contrast, two beta 2 antagonists (butoxamine and ICI 118,551) significantly retarded disease onset and reduced the severity of joint injury. When reserpine or butoxamine treatment was initiated after the onset of clinically apparent arthritis, it was still possible to favorably influence the course of the disease. These data indicate an important contribution of the beta 2-adrenergic receptor to joint injury in experimental arthritis.